A systematic mapping review of interventions to improve adolescent mental health literacy, attitudes and behaviours. Issue 6 (3rd January 2021) - Patafio, Brittany; Miller, Peter; Baldwin, Ryan; Taylor, Nicholas; Hyder, Shannon
Abstract: Aim: The onset of mental illness is most common in adolescence, therefore mental health promotion efforts frequently target this age group. Evaluation literature in this area is largely segmented into specific domains in terms of settings, countries, and/or groups of young people, but an overall understanding and comparison across these areas is lacking. The current review aims to provide such an overview of interventions/programs which attempt to improve adolescents' mental health literacy, attitudes/stigma and behaviours. Methods: A systematic mapping review synthesized the strengths and weaknesses of published interventions/programs to improve mental health outcomes in youth. Ten databases and grey literature sources were searched, and results were categorized according to sample, location/setting, type of information presented, delivery and testing procedures, mental health outcome/s evaluated, and limitations. Results: One hundred and forty articles met the inclusion criteria; 126 were original records and 14 were reviews. Mental health literacy and attitudes/stigma were examined most frequently, and studies were predominantly conducted in school‐based environments and high income economies. Intervention/program effectiveness varied across outcome/s measured, setting, and control group usage, with mental health literacy exhibiting the most positive changes overall. Common limitations included no long‐term follow up or control group inclusion. Conclusions: Despite generally positive changes seen throughout studies in this area, effectiveness differed across a range of methodological domains. Most research is conducted in schools and higher income economies, but the lack of investigation in other contexts (i.e., internet or community) or lower income countries suggests our understanding in this area is constrained.